2015
DOI: 10.1080/13607863.2015.1040723
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cognitive impairment in patients with newly diagnosed type 2 diabetes: a cross-sectional study

Abstract: Age, verbal intelligence, female gender and HbA1c are associated with cognitive performance in T2DM soon after diagnosis. Previously reported associations with depression and inflammatory markers may occur later as causes or consequences of T2DM. Longitudinal analyses are needed to assess potentially modifiable factors predicting cognitive decline in early T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Four studies were found to have critical risk of bias, meaning they were likely to be too biased to allow for any contribution to the research question. [ 26 ] All four studies were cross-sectional analyses, and in total accounted for less than 2,000 participants with diabetes from Australia, [ 28 ] Canada, [ 35 ] the UK, [ 42 ] and US. [ 31 ] There was no clear trend among these studies with respect to an association between depression and cognition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were found to have critical risk of bias, meaning they were likely to be too biased to allow for any contribution to the research question. [ 26 ] All four studies were cross-sectional analyses, and in total accounted for less than 2,000 participants with diabetes from Australia, [ 28 ] Canada, [ 35 ] the UK, [ 42 ] and US. [ 31 ] There was no clear trend among these studies with respect to an association between depression and cognition.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 ] Similarly, another reported no relationship between depressive symptoms and TICS-M scores. [ 42 ] Lastly, one study found that reaction times were significantly faster among participants with comorbid depression–the only study out of fifteen to find a positive association between depression and cognition ( Table 3 ). [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previous neuroimaging studies of T2DM patients show that brain atrophy appears in the hippocampus, amygdala, and prefrontal areas, and it frequently occurs in elderly patients with long duration of diabetes 23 . Cognitive impairment across multiple domains of cognition has been demonstrated in T2DM, and involve executive functioning, memory, attention, information processing and visuospatial abilities 24 27 , even in studies with middle-age T2DM patients 28 31 . In line with these cognitive dysfunctions, neuroimaging studies show the functional brain changes in early stage T2DM as well, including altered resting-state functional connectivity and task-related neuronal activity 32 35 .…”
Section: Introductionmentioning
confidence: 99%
“…An explanation might be that though there have been reports on a positive association of high-normal glucose levels in diabetes-free subjects of the general population with hippocampal atrophy (Weinstein et al 2015 ), most studies indicate that these changes are primarily seen in those patients with longer disease duration and higher HbA1c levels (Ebady et al 2008 ; Lin et al 2013 ) and those with late sequelae such as micro- or macrovascular damage (Wessels et al 2006 , Moulton et al 2016 ) and peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%